The approximation behavior of the variance multipliers using the regular standard - Bula'ras, Salih Mahmud; Hiyour, Muhammad; Zanir, Khalid Hussein; Al Sharif, Bahr Qasim (Journal of natural sciences, life and applied sciences, 2017)
The paper deals with the study of the Asymptotic behavior of Solutions for the Parabolic Quasi variation inequalities and their Convergence, where we the estimate between the discrete solution calculated in the step end of the time and the asymptotic behavior solution in uniform norm was evaluated.